THE RESPONSIVENESS OF CHILDHOOD/ADOLESCENT CHRONIC MYELOID LEUKAEMIA PATIENTS OF PAKISTANI ORIGIN TO TYROSINE KINASE INHIBITOR - Shah, Syed Yar Muhammad; Ajmal,; Darakhshanda Nawaz,; Aiman Usman Lodhi,; Jawad ur Rehman,; Rehman Bahadar,; Zaheer Ahmad,; Faizan Banaras, (Journal of Ayub Medical College Abbottabad, 2023)
Chronic myelogenous leukaemia is a disease in which bone marrow produces too many white blood cells. It is more common in middle age and its incidence is rare in children. Imatinib is the standard first-line treatment in chronic myeloid leukaemia. It improved the prognosis with lesser side effects. Our point of interest is to highlight its role in the paediatric age group. we present case series of a patient with chronic myeloid leukaemia responsive to imatinib. Because of the rare incidence of chronic myeloid leukaemia in this age room limited studies to explore the role of treatment modalities in the paeds group. Our case series highlights imatinib's effectiveness in treatment and improving the prognosis of the disease in this age group.